Health Literacy Influences Heart Failure Knowledge Attainment but Not Self-Efficacy for Self-Care or Adherence to Self-Care over Time - Aleda M. H. Chen; Karen S. Yehle; Nancy M. Albert; Kenneth F. Ferraro; Holly L. Mason; Matthew M. Murawski; Kimberly S. Plake (Hindawi Limited, 2013)
Background. Inadequate health literacy may be a barrier to gaining knowledge about heart failure (HF) self-care expectations, strengthening self-efficacy for self-care behaviors, and adhering to self-care behaviors over time. Objective. To examine if health literacy is associated with HF knowledge, self-efficacy, and self-care adherence longitudinally. Methods. Prior to education, newly referred patients at three HF clinics (N=51, age: 64.7±13.0 years) completed assessments of health literacy, HF knowledge, self-efficacy, and adherence to self-care at baseline, 2, and 4 months. Repeated measures analysis of variance with Bonferroni-adjusted alpha levels was used to test longitudinal outcomes. Results. Health literacy was associated with HF knowledge longitudinally (P<0.001) but was not associated with self-efficacy self-care adherence. In posthoc analyses, participants with inadequate health literacy had less HF knowledge than participants with adequate (P<0.001) but not marginal (P=0.073) health literacy. Conclusions. Adequate health literacy was associated with greater HF knowledge but not self-efficacy or adherence to self-care expectations over time. If nurses understand patients' health literacy level, they may educate patients using methods that promote understanding of concepts. Since interventions that promote self-efficacy and adherence to self-care were not associated with health literacy level, new approaches must be examined.